TINJAUAN KUAT TEKAN BETON DENGAN MENGGUNAKAN SERAT BENDRAT SEBAGAI BAHAN TAMBAH - Hermansyah; Moh Ihsan Sibgotuloh (Program Studi Informatika Universitas Teknologi Sumbawa, 2019)
The more widespread use of concrete construction and the increasing scale of construction, the higher the demand for materials used in concrete mixes. One of the innovations of concrete is fiber concrete. Hope the addition of fiber in concrete mixes such as wire fiber to increase the compressive strength value of normal concrete that is often used, so the purpose of this study is to determine the effect of adding wire fiber to the ease of working (workability) of the concrete mixture and to determine the effect of adding wire fiber to concrete compressive strength. In this study, the fiber used is the type of wire fiber with a diameter of 1 mm and a length of 60 mm. Fiber variations used are 0%, 0.4%, 0.6% and 0.8% based on the weight of fresh concrete. Concrete mix (mix design) using SNI 03-2834-2000 about concrete mix planning with a test life of 28 days. The test results showed that the lowest average compressive strength of 12,291 MPa occurred at 0% variation and the highest average compressive strength value of 20,656 MPa at 0.8% fiber variation. The increase is caused by the even distribution of fibers in the concrete produced, the higher the variation that is given by the fiber, the better the fiber spread, from these fibers provide a fairly good contribution to the fiber concrete